1997
DOI: 10.1074/jbc.272.22.14394
|View full text |Cite
|
Sign up to set email alerts
|

Interleukin-4 and -13 Inhibit Tumor Necrosis Factor-α mRNA Translational Activation in Lipopolysaccharide-induced Mouse Macrophages

Abstract: The production of tumor necrosis factor-␣ (TNF-␣) by lipopolysaccharide (LPS)-stimulated macrophages can be markedly inhibited by the two closely related cytokines, interleukin (IL)-4 and IL-13. To investigate the molecular mechanism of this inhibition, we analyzed the effect of the two cytokines on TNF-␣ production and TNF-␣ mRNA accumulation in the mouse macrophage cell lines RAW 264.7 and J774 stimulated by LPS. Whereas LPS-induced TNF-␣ production is strongly suppressed by both cytokines, TNF-␣ mRNA accumu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
57
0
1

Year Published

1998
1998
2015
2015

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 106 publications
(63 citation statements)
references
References 30 publications
5
57
0
1
Order By: Relevance
“…From the results obtained with other systems, indications are that the process of down-regulation of TNF-c~ by IL-4 occurs at the translational level (17,21). The lack of a significant difference in the mucosal level of IL-4 between the alcohol diet and the control groups observed in our studies may indicate that chronic alcohol ingestion exerts the detrimental effect on this regulatory cytokine expression, causing dysregulation of proinflammatory cytokine, TNF-c~, production, and thus triggering the apoptotic events.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…From the results obtained with other systems, indications are that the process of down-regulation of TNF-c~ by IL-4 occurs at the translational level (17,21). The lack of a significant difference in the mucosal level of IL-4 between the alcohol diet and the control groups observed in our studies may indicate that chronic alcohol ingestion exerts the detrimental effect on this regulatory cytokine expression, causing dysregulation of proinflammatory cytokine, TNF-c~, production, and thus triggering the apoptotic events.…”
Section: Resultsmentioning
confidence: 99%
“…While the relationship between the prolonged and excessive consumption of alcohol and the increased levels of proinflammatory cytokines such as TNF-c~, IL-2, IL-6 and IL-12 is well established (19), less is known about the effect of chronic alcohol ingestion on the expression of the regulatory cytokines such as IL-4, the major function of which is the repression of inflammatory cytokine production (17,20). From the results obtained with other systems, indications are that the process of down-regulation of TNF-c~ by IL-4 occurs at the translational level (17,21).…”
Section: Resultsmentioning
confidence: 99%
“…Interleukin-4 (IL-4) is a prototypical anti-inflammatory cytokine [49,50]. Furlan et al and Poliani et al had shown that HSV-expressed IL-4 prevents the development of autoimmune encephalitis in Biozzi AB/H mice and in rhesus monkeys [51].…”
Section: Gene Transfer To Modulate the Neuroimmune Response In Chronimentioning
confidence: 99%
“…IL-4 plays an essential role in T and B cell differentiation where it is critical for initiating type 2 immune responses (1,2). In addition, IL-4 is recognized as an antiinflammatory cytokine that modulates macrophage activity through the suppression of proinflammatory cytokine expression (3)(4)(5)(6). Macrophage-induced cytokines are important for differentiation of Th1-type cells and as such IL-4 may be essential for the regulation of Th1-type responses (2,7).…”
Section: Il-4 and Il-12 Regulate Proteoglycan-induced Arthritismentioning
confidence: 99%